Foundations of landscape architecture : integrating form and space using the language of site design - Booth, Norman K. 4 0 16; 5 (Hoboken, N.J. : John Wiley & Sons, 2012)
Introduces concepts, typologies, and rudimentary principles of form and space, and includes designs for projects such as parks, campuses, and memorials.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Landscape architecture. -- 20; 20; 2